2018
DOI: 10.12659/aot.908771
|View full text |Cite
|
Sign up to set email alerts
|

The Pre-Transplant Profile of Cardiovascular Risk Factors and Its Impact on Long-Term Mortality After Liver Transplantation

Abstract: BackgroundCardiovascular disease (CVD) is an important aggravating factor for orthotopic liver transplantation (OLT) outcomes. CVD still seems to be one of the most common cause of death in the long-term post-transplant period. Nevertheless, there are some limited data regarding the optimal strategy of risk assessment during OLT candidate evaluation.Material/MethodsRoutine pre-transplant cardiac workup in 360 patients with end stage liver disease (ESLD) included electrocardiogram, echocardiography, and exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…For liver transplant recipients, heart diseases are an important risk factor for perioperative mortality [1]. Approximately 7-21% of deaths following liver transplantation are related to cardiovascular events [2].…”
Section: Introductionmentioning
confidence: 99%
“…For liver transplant recipients, heart diseases are an important risk factor for perioperative mortality [1]. Approximately 7-21% of deaths following liver transplantation are related to cardiovascular events [2].…”
Section: Introductionmentioning
confidence: 99%
“…The standard pre-LT work-up includes electrocardiogram and transthoracic echocardiography [6], in order to identify cardiac disorders that, untreated, would worsen the LT outcome. In addition, patients older than 50 years, or with cardiovascular risk factors (hyperlipidemia, hypertension, diabetes, and smoking), should undergo noninvasive stress testing and cardiologic evaluation, in order to assess underlying coronary artery disease [6,8,27]. Patients with proven ischemia from the stress test (for example: stress echocardiography with dobutamine) are referred to the multidisciplinary team for further investigations, like coronary angiography with revascularization, if there is more than 70% coronary artery obstruction [23].…”
Section: Cardiovascular Function Before and After Liver Transplantmentioning
confidence: 99%
“…A recently published study [27] demonstrated that the prevalence of traditional CV risk factors among LT patients is around 23%; the most common being hypertension and diabetes. However, studies failed to demonstrate a significant association between the risk factors and mortality, due to CV events within the first 30 days after LT [14].…”
Section: Cardiovascular Function Before and After Liver Transplantmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no consensus on the preferred screening test to detect CAD in the pre-LT population nor for post-LT cardiac evaluation. The methods of cardiac assessment differ from site to site [ 3 , 8 , 17 ]. The American Heart Association and the American College of Cardiology Foundation suggest non-invasive stress testing following cardiovascular risk assessment for patients without active cardiac disease [ 18 ].…”
Section: Introductionmentioning
confidence: 99%